Research on Inertial Isolation Rotation Modulation of Dual-Axis Inertial Navigation Based on Multi-Error Coupling Characteristics - Bo Zhang; Changhua Hu; Silin Hou; Jianxun Zhang; Jianfei Zheng; Xuan Liu (Aerospace)
Currently, research on the rotational modulation of dual-axis inertial navigation for isolated carrier motion does not provide sufficient solutions for the compensation of the gyroscope scale factor error caused by the Earth’s rotation. Moreover, it is primarily applied to ships with low maneuverability and has not yet been implemented in the field of pure inertial guidance weapons. A dual-axis inertial isolation rotation modulation method is proposed to address this issue, taking into account the application characteristics of long-endurance guided weapons. An analysis of the system error characteristics under the coupling of multiple error sources acting on IMU was conducted, and it was found that the angular velocity of the inertial isolation carrier can significantly reduce the output error of the IMU. A dual-axis inertial isolation shaft system installation error compensation algorithm was designed, and an improvement was made based on the traditional sixteen-sequence rotation scheme to compensate for the projection components of the Earth’s rotation and carrier motion on the inner and outer frame rotation axes, achieving the inertial isolation rotation modulation function of dual-axis inertial navigation. Based on the attitude changes in long-range guided weapons, Monte Carlo simulation verification was conducted, and the results showed that this scheme can improve inertial navigation accuracy by 10% to 20%.